Evaluating the process of partnership and research in global health: Reflections from the STRIPE project - Kalbarczyk, Anna; Rao, Aditi; Mahendradhata, Yodi; Majumdar, Piyusha; Decker, Ellie; Binte Anwar, Humayra; Akinyemi, Oluwaseun O.; Rahimi, Ahmad Omid; Kayembe, Patrick; Alonge, Olakunle O. (BMC, 2022)
This article was published in BMC Public Health by BMC [© The Author(s). 2020 Open Access This article is licensed under a Creative Commons Attribution 4.0 International License] and the definite version is available at: https://doi.org/10.1186/s12889-020-08591-y The Journal's website is at: https://bmcpublichealth.biomedcentral.com/articles/10.1186/s12889-020-08591-y